BO‘LAJAK INFORMATIKA O‘QITUVChILARINI TAYYORLAShDA FANLARARO TARMOQ TEXNOLOGIYALARIDAN FOYDALANISh - Alaminov, M.X. (SCIENCE and SOCIETY, 2025)
The article presents a methodology for teaching network technologies to future computer science teachers. This methodology is based on an interdisciplinary approach, which presents modern trends in the development of network technologies aimed at developing the knowledge and skills necessary for designing, creating, managing local computer networks, solving server-related issues, choosing a firewall type, creating network educational resources and placing them on the Internet. The results of applying this methodology in the process of training future computer science teachers are presented.